STRUKTUR KEPEMILIKAN DAN NILAI PERUSAHAAN: (STUDI PADA PERUSAHAAN MANUFAKTUR YANG LISTING DI BURSA EFEK INDONESIA) - Restu Fahdiansyah; Jihadil Qudsi; Adam Bachtiar (Jurnal Varian, 2018)
The purpose of company management in general is to generate profit, but furthermore the management of the company is required to improve the welfare of the owners of the company or in this case the shareholders. To achieve these objectives, it is necessary to have ownership structures that can provide maximum supervision to managers in order to carry out their duties to improve the welfare of the owners of the company through increasing the value of the company. This is in accordance with the agency theory developed by Jensen Meckling stating that the manager as an agent delegated by the owner of the company to manage the company. In the process of managing the company, according to Jensen Meckling there is possible occurrence of agency problems, which arise because of the tendency of managers to not always make decisions that aim to meet the interests of principals or owners of the company to the fullest. To align the interests of managers and owners of the company so as to reduce agency problems, it is necessary to have a good ownership structure, capable of monitoring the performance of management in meeting the interests of the owner of the company. Therefore, this study would like to examine how ownership structures proxied with institutional ownership and managerial ownership can influence the value of firms that can ultimately have an impact on increasing shareholder wealth. This study tested 71 manufacturing companies listed on the Indonesian Stock Exchange in 2016 using multiple regression analysis techniques. The test results show the significant influence of variables with institutional ownership and managerial ownership of firm value, which shows that the ownership structure that allows the owner of the company to supervise the performance of the company's management can have an impact on the increase of company value.